Development of artificial meteor for observation of upper atmosphere. (April 2016) - Watanabe, Masaki; Sahara, Hironori; Abe, Shinsuke; Watanabe, Takeo; Nojiri, Yuta; Okajima, Lena
Abstract: This study proposes a method for the observation of the upper atmosphere using an artificial meteor injected by a mass driver installed on a microsatellite. The mass driver injects a pill at a velocity of 200 m/s and deorbits it into the atmosphere. The emission of the pill can then be observed from the ground at the necessary time and location. This approach could contribute to a better understanding of the global environment as well as different aspects of astronomy and planetary science. To realize the proposed method, the required size and emission of the pill have to be determined. Therefore, we conducted flow-field simulations, spectroscopic estimations, and an experiment on an artificial meteor in the arc heater wind tunnel at the Institute of Space and Astronautical Science in the Japan Aerospace Exploration Agency (ISAS/JAXA). From the results, we confirmed that the light emission could be observed as a shooting star by the naked eye and thus verified the feasibility of the method. Abstract : Highlights: This study proposes a method for the observation of the atmosphere using an artificial meteor. We conducted flow-field and spectroscopic estimations, an experiment in the arc heater. We confirmed that the light emission could be observed by the naked eye on the ground.